Acute effect of active stretch exercises on agility and strength in 10 to 14-year-olds children a randomized study - Silva Filho, José Nunes da (2020)
The current literature still debates on which type of settings stretching exercises can promote detrimental effects on other physical capacities. Such effects seem to be related to several factors which requires researchers to verify such influences in terms of each specific context. As indoor soccer requires a mix of physical capacities, we studied the influence of static stretching in indoor football players. This manuscript addressed the acute effects of static stretching exercises (SSE) on muscle power and agility of 10 to 14-year-olds children practicing indoor soccer. This study is a randomized controlled clinical trial. Forty-six children, participant of a futsal training program, performed pre- and post-tests on horizontal jumping measuring muscle power and the shuttle run test measuring agility separated by no exercise (control group, CG) or SSE (experimental group - GE). The results pointed out a detrimental effect on the horizontal jumping but not on the shuttle run test which showed a slight improvement. Considering the effect on the shuttle run to be a familiarization effect, we then observed effects of stretching on muscle power but not agility. As our sample is composed of trained individuals and following similar results in the literature we discussed these results in terms behavioral mechanisms that avoid detrimental effects of SSE provided training. SSE is detrimental to muscle power but not to agility in young trained individuals of indoor soccer. These results were interpreted in terms of potential mechanisms that training afford to individuals. Namely, compensatory behavioral strategies to maintain performance.